Determination of carbamate pesticide methomyl using acetylcholinesterase / MWNTs-Chitosan modified glassy carbon electrode - Zhao, Yan; Zhang, Shu-Ping; Ma, Jie; Leng, Kai-Liang; Labuda, Jan (Univerzita Pardubice, 2012)
An electrochemical biosensor based on immobilization of acetylcholinesterase (AChE) onto multi-walled carbon nanotubes (MWNTs) and chitosan (CS) modified glassy carbon electrode (GCE) has been prepared for the rapid determination of a carbamate pesticide Methomyl. AChE was immobilized via a layer-by-layer self-assembly modification technique with CS. Inhibition effect of methomyl on the AChE activity was proportional to its concentration within the range from 10-10 to 10-3 g L-1 with the detection limit of 10-11 g L-1. The {AChE/CS}/{MWNTs/CS}/GCE biosensor represents an effective and alternative tool for the determination of pesticide residues in environment and food samples.
Keywords: electrochemical biosensor; methomyl; acetylcholinesterase; chitosan; carbon nanotubes